ANALYSING THE POTENTIAL OF CORAL REEF ECOSYSTEMS FOLLOWING THE COVID-19 PANDEMIC IN BONDALEM, BULELENG, BALI - Made Dwipa Kusuma Maharani; Muhammad Sumsanto; I Nyoman Dodik Prasetia; Dewi Wulandari (Jurnal Perikanan Unram, 2024)
Coastal and marine areas have considerable biological resource potential, because they are supported by three main ecosystems, namely mangrove ecosystems, seagrass beds and coral reefs. Coral reefs are one of the coastal ecosystems that contribute greatly to coastal areas. But behind the great potential, it is also very vulnerable to damage, both caused by nature and human activities on land and in sea waters. As an effort to maintain the existence of these ecosystems, ecosystem monitoring is needed to find out how much potential is still available in the coastal area. The purpose of this study was to determine and provide information related to the potential and condition of coral reefs in Bondalem Village. This research used descriptive quantitative method with purposive sampling technique. The data taken is primary data that includes observations of coral reefs based on the form of growth (lifeform). Coral reef data collection was carried out using the UPT (Underwater Photo Transect, Underwater Photo Transect) method. The results obtained, coral reefs at the observation station have a total of 18 lifeforms. The percentage of coral cover obtained at a depth of 3 meters has a coral cover ranging from 35.34%, while at a depth of 10 meters the result of coral cover is 26.30% (medium category). The coral reef ecosystem uniformity index ranges from 0.96 - 0.97 (high). The diversity index of coral reef ecosystems in Bondalem Village ranged from 1.25 which is included in the relatively medium category (1<H'<3). The dominance index of coral reef ecosystem in Bondalem Village ranged from 0.064 - 0.066 (low).